2008
DOI: 10.1177/021849230801600511
|View full text |Cite
|
Sign up to set email alerts
|

Verapamil and Nitroglycerin Improves the Patency Rate of Radial Artery Grafts

Abstract: The best way to prevent spasm of the radial artery is still under investigation. We retrospectively compared the effectiveness of topical verapamil-nitroglycerin with papaverine in preventing graft spasm in 215 patients who underwent isolated conventional coronary artery bypass using a radial artery. Postoperative angiographic data were successfully collected in 116 patients. Perioperative radial artery graft spasm was observed in 2 patients in the papaverine group and 1 in the verapamil-nitroglycerin group; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…In a study by Yoshizaki et al [115] including 215 patients, topical use of VG solution led to better patency of RA grafts than papaverine, which was confirmed by angiography more than a year after the operation. Moreover, although papaverine causes vasorelaxation through multiple mechanisms: phosphodiesterase inhibition, decreased calcium influx, and inhibition of the release of intracellularly stored calcium [129], it is very acid, resulting in damaged endothelium [130][131][132].…”
Section: Ra Characteristicsmentioning
confidence: 81%
See 1 more Smart Citation
“…In a study by Yoshizaki et al [115] including 215 patients, topical use of VG solution led to better patency of RA grafts than papaverine, which was confirmed by angiography more than a year after the operation. Moreover, although papaverine causes vasorelaxation through multiple mechanisms: phosphodiesterase inhibition, decreased calcium influx, and inhibition of the release of intracellularly stored calcium [129], it is very acid, resulting in damaged endothelium [130][131][132].…”
Section: Ra Characteristicsmentioning
confidence: 81%
“…Reversible spasm is more frequent than is believed and unstable hemodynamics can declare spasm only in grafts supplying with blood critical coronary territories [115]. Moreover, the mechanism of severe spasm in the RA appears to be more difficult to reverse compared with the LITA [116].…”
Section: Ra Characteristicsmentioning
confidence: 99%
“…Yoshizaki and coworkers reviewed angiographic results among 116 CABG patients who had RA grafts and were treated either with verapamil-nitroglycerin or papaverine. 53 Results showed that papaverine was significantly associated with RA graft occlusion. Among patients randomized to either continue or suspend diltiazem therapy 1 year after RA grafting, Gaudino and colleagues showed that at 5-year follow-up there was no difference in angiographic patency rates between groups.…”
Section: Pharmacological Preparation and Graft Storagementioning
confidence: 99%
“…[ 4 15 ] Some of the drug combinations such as intraluminal or topical administration of calcium antagonists or milrinone with NTG have demonstrated synergistic effects on vasodilation. [ 15 16 ] Papaverine produces vascular relaxation through several mechanisms, including inhibition of phosphodiesterase and release of intracellularly stored calcium resulting in decreased calcium influx. [ 17 ] Intraluminal and periarterial injections have been shown to induce more vasodilatation than the topical application of papaverine.…”
Section: Discussionmentioning
confidence: 99%